Femtolaser refractive autokeratoplastic: first results and prospects - H. V. Sitnik; A. Yu. Slonimsky; Yu. B. Slonimsky (Oftalʹmologiâ)
Purpose. Development of a new method of autokeratoplasty using of femtosecond laser in patients with advanced keratoconus and evaluation of early results of treatment.Patients and methods. 17 patients with advanced stable keratokonus were included in the study (15 men, 2 women) mean age 33±8.4 years old. Stage III of keratokonus was diagnosed in 3 eyes, stage IV was revealed in 14 eyes. Minimal corneal thickness was 381±33.82 μм, keratometric indices Ks 60.1±5.7 D, Kf 54.8±5.8 D, cylinder 9.1±3.8 D. Femtolaser-assisted refractive autokeratoplasty (FRAK) was performed with the use of «IntraLase 60 kHz». The idea of our method consists in performing of 2‑step resection of corneal stroma using femtosecond laser. Firstly, circular corneal cut should be made at an angle to the surface is fulfilled on distance 1.5‑2.0 mm from the limbus to a depth of up to 90 % of stroma thickness. Secondy, a second circular corneal cut — perpendicular to the surface, on distance from 150 to 300 mm from the first one, is performed so that the cuts intersected at a predict depth and the circular corneal flap with wedge-shaped profile was formed. After flap removal corneal wound is suturing with the single buried sutures 10‑0.Results. Operation and early post-op period were uneventful. MeanUCVA significantly improved from 0.07±0.03 to 0.26±0.13 to 3 months after surgery. Between 3 to 6 months after surgery, we observed the increasing of visual functions (like UCVA and BCVA). The improvement of BCVA was observed in 94.1 %, and in 76.5 % of cases the increase was more than 3 lines. The cylindrical component decreased from 9.1±3.8 to 5.4±2.5 D.Conclusions. FRAK is a new method for the treatment of stable advanced keratoconus, which helps to improve optical capacity of cornea, allows to save the patient’s own cornea, improves both UCVA and BCVA. Non-penetrating nature of the operation helps to minimize the complications. Femtosecond laser for corneal stroma resection provides high accuracy and predictability. Further research is needed to determine long-term outcomes.